Nil-Per-Os Days and Necrotizing Enterocolitis in Extremely Preterm Infants - Kirtsman, Maksim; Yoon, Eugene W.; Ojah, Cecil; Cieslak, Zenon; Lee, Shoo K.; Shah, Prakesh S. (American Journal of Perinatology, 2015)
Objective This study aims to evaluate the association between nil-per-os (NPO) days and development of necrotizing enterocolitis (NEC) in extremely preterm neonates (<29 weeks gestational age).Study Design A case–control study of 234 extremely preterm neonates who developed stage II or III NEC and 467 matched control infants admitted to participating sites in the Canadian Neonatal Network between 2010 and 2011 was conducted. The number and percentage of NPO days before the development of NEC was compared with the equivalent period in control infants using logistic regression.Results Infants with NEC were NPO on average 5.6 days (28% of days before NEC) versus 3.7 days (19% of equivalent days; p < 0.01) among controls. NEC cases required more days of inotropic support, antibiotic use, and had higher rates of patent ductus arteriosus (PDA). After adjusting for inotrope use, PDA, antibiotics, and severity of illness, for each additional NPO day the adjusted odds for NEC increased by 1.08 (95% confidence interval: 1.04–1.12).Conclusion Among extremely preterm neonates, those who developed NEC were NPO for a longer period of time than control infants who were NEC-free. We speculate that delayed initiation or interruption of feeding may be a potent risk factor for NEC.
Keywords: enteral nutrition; gut colonization; infant; premature; intestinal microbiome